TRANSLATING SINGULAR THIRD PERSONAL PRONOUNS: OBSERVATIONS FROM THE INDONESIAN AND JAPANESE CLASSROOMS - Arunarsirakul, Angela (Lingua, 2018)
Pertimbangan status bahasa Inggris sebagai bahasa global membuat bahasa tersebut dihargai di seluruh dunia, serta banyak orang yang inginmempelajarinya sampai pada tingkat kemahiran tertentu. Namun, sama halnya belajar bahasa lain bahwa belajar bahasa Inggris bukan hal yang mudah, seperti yang saya buktikan dari pengalaman mengajar ketika di Indonesia dan Jepang. Berdasarkan pengamatan sebagai bukti anekdot, ada beberapa pertimbangan topik yang sangat spesifik yaitu kata ganti orang ketiga tunggal dan menganalisis tantangan yang muncul pada saat saya mengajar topik tersebut bagi siswa-siswa asing ketika berada di Indonesia dan JepangWith English’s status as a global language, learning the language has become increasingly important with language fluency highly valued and prized around the world. However, as is the case with learning any other language, learning English is not an easy task, as can be attested to based on my teaching experiences in Indonesia and Japan. Drawing upon observations as anecdotal evidence, I consider a very specific topic - namely, singular third personal pronouns - and analyze the specific set of unique challenges that my Indonesian and Japanese students face with this part of speech.